Голубянки фауны СССР, относимые к роду Chilades (Lepidoptera, Lycaenidae) - Некрутенко, Ю.П. (Вестник зоологии, 1984)
The Blue Butterflies of the USSR Fauna, Assigned to the Genus Chilades (Lepidoptera, Lycaenidac). Nekrutenko Yu. P.— Vestn. zool., 1984, No. 3. Lachides gen. n. is
established to inciude Lycaena galba Lederer, 1855 (type-species) and Lampides confracta Butler, 1880, unanimously assigned in’ the recent literature fo the genus Chilades Moore. Lycaena phiola Groum-Grshimailo, 1890 is treated as a subspe-
cies of L. galba. L. contracta is resurrected from the synonymy of Hesperia parrhasius
Fabricius, 1793; consequently, Chilades lempkei Blom, 1979 is sunk in synonymy
of L. contracta. Lettotypes of all species-group nominal taxa considered are designated
in collections of Zoologisches Museum an der Humboldt-Universitat zu Berlin (galba),
Zoological Institute, USSR Academy of Sciences, Leningrad (phiala) and British Museum
(Natural History), London (contracta).